Maternal oxygenation and neonatal outcome in pregnant women with COVID-19: A case series of 20 patients - Takumi Yamaguchi; Tomoaki Fujii; Hiroyuki Hirate; Yusuke Ota (Wolters Kluwer Medknow Publications, 2023)
Purpose: Management of delivery in pregnant women with coronavirus disease 2019 (COVID-19) is mainly based on extrapolated evidence or expert opinion. This study aimed to assess the clinical manifestations and maternal and perinatal outcomes of COVID-19 during pregnancy. Methods: We retrospectively reviewed the cases of 20 pregnant women infected with the new severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Their demographic data and clinical characteristics, including symptoms, laboratory examination, and imaging findings, were evaluated. We also assessed the delivery method and timing and clinical courses of mothers, including oxygenation and treatment for COVID-19, as well as neonatal outcomes. Results: The most common symptoms were fever (65%) followed by cough (45%). Seven cases (35%) of preterm birth were observed. Eight patients (40%) required oxygen administration during pregnancy. Among them, two patients (10%) required a high-flow nasal cannula, and one patient (5%) required venovenous extracorporeal membrane oxygenation (VV-ECMO). No maternal death was observed; however, one instance of severe neonatal asphyxia and one intrauterine fetal death were observed. Conclusion: Although most pregnant women with COVID-19 were discharged without any major complications, some cases became severe. Therefore, the timing and method of delivery should be considered for each case to control maternal and infant respiratory conditions.